2012
DOI: 10.1124/dmd.111.044404
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of the Antiretroviral Drug Etravirine: Metabolite Identification, Reaction Phenotyping, and Characterization of Autoinduction of Cytochrome P450-Dependent Metabolism

Abstract: ABSTRACT:Etravirine (ETR) is a second-generation non-nucleoside reverse transcriptase inhibitor prescribed for the treatment of HIV-1. By using human liver microsomes (HLMs), cDNA-expressed cytochromes P450 (P450s), and UDP-glucuronosyltransferases (UGTs), the routes of ETR metabolism were defined. Incubations with cDNA-expressed P450 isozymes and chemical inhibition studies using HLMs indicated that CYP2C19 is primarily responsible for the formation of both the major monohydroxylated and dihydroxylated metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…The third donor (age 28, female) demonstrated a 2.5-fold increase in CYP3A4 mRNA levels with no other changes. It was previously reported that etravirine modulates CYP3A4 expression in a pregnane x receptor (PXR)-dependent manner [10]. With this in mind, PXR mRNA expression in the colon tissues was measured and showed positive correlation with the observed changes in CYP3A4 mRNA, indicating that there may be a relationship between PXR levels and dapivirine-treatment dependent CYP3A4 mRNA expression changes in colon tissue (Figure 9D).…”
Section: Resultsmentioning
confidence: 59%
“…The third donor (age 28, female) demonstrated a 2.5-fold increase in CYP3A4 mRNA levels with no other changes. It was previously reported that etravirine modulates CYP3A4 expression in a pregnane x receptor (PXR)-dependent manner [10]. With this in mind, PXR mRNA expression in the colon tissues was measured and showed positive correlation with the observed changes in CYP3A4 mRNA, indicating that there may be a relationship between PXR levels and dapivirine-treatment dependent CYP3A4 mRNA expression changes in colon tissue (Figure 9D).…”
Section: Resultsmentioning
confidence: 59%
“…Oxidative metabolism did not appear to be shunted to glucuronic acid conjugation, as the glucuronides that were detectable in the hepatocyte medium, namely, metabolites M5 and M6, also did not exhibit an increase in abundance over the 24 h of incubation. Although we have previously reported that autoinduction of etravirine metabolism is readily detectable following 24 h of incubation with primary human hepatocytes (17), longer treatment times may be required to observe this effect using RPV. For instance, CYP3A4 protein may not have yet been elevated over the time points that we measured.…”
Section: Figmentioning
confidence: 88%
“…A recent report demonstrated that RPV, similar to the nonnucleoside reverse transcriptase inhibitors etravirine and efavirenz, was able to activate the pregnane X receptor in primary human hepatocytes (17). The pregnane X receptor is a key regulator of drug-metabolizing enzymes, including CYP3A and UGT1A isozymes (22)(23)(24).…”
Section: Figmentioning
confidence: 99%
“…ETR is also a weak inducer of CYP3A4 [16] (by increasing the abundance of CYP3A4 mRNA in a pregnane X receptor (PXR) dependent manner) [17] and an inhibitor of CYP2C9, CYP2C19 and P-gp [15, 16, 18]. It has been previously demonstrated that the CYP3A5 gene is inducible by mechanisms similar to those involved in CYP3A4 induction, involving constitutively activated receptor (CAR) and PXR [19].…”
Section: Introductionmentioning
confidence: 99%